Thermal conductivity and conditioning of grey expanded polystyrene foams. Issue 6 (November 2020) - Simpson, A; Rattigan, IG; Kalavsky, E; Parr, G
This article focuses on the thermal conductivity of 50 mm thick silver grey (infrared absorbing) expanded polystyrene (EPS) foam boards blown with pentane. The effect of short-term ageing from the point of production, by ambient conditioning at 23°C/50% RH, is compared to conditioning at an elevated temperature of 70°C. The declared thermal properties of the product and CE certification are fulfilled by the requirements of the European EPS product standard and SG19 Guidance. Measured thermal conductivity levels within 1% of the final value are acceptable and considered representative throughout the economic life of the product. Levels within the criteria were determined for 50 mm silver EPS after conditioning for 5 days at an elevated temperature of 70°C, whereas for conditioning at 23°C/50% RH the time taken was 23 days. The latter time is in good accord with retesting retained grey EPS boards of similar density and up to 9 years old, after initial testing 22 days from production, and conditioning at 23°C/50% RH. Elevated temperature conditioning increases the rate of diffusion of the blowing agent, but there has been concern about EPS beads softening above 60°C. Although there is little evidence from scanning electron microscopy of significant increase in perforation of the cell membranes at elevated temperatures, there is some indication of a small increase in wrinkling of the walls and intercell skeletal strands at 60°C and 70°C. It takes longer to eliminate the pentane gas by conditioning at 23°C/50% RH but there is no risk of material change from heat conditioning.